Molecular Docking and Antimalarial Evaluation of Natural Phenolics and Their Derivatives on Plasmodium falciparum Lactate Dehydrogenase as Schizonticidal Drug Candidates - Bassey Asuquo, Andong; Samuel Onyeka, Onyechi; Ekemini Victor, Etukakpan; Mfonobong Effiong, Umoh; Anthony Chidera, Pascal; Johnson, Ekarika; A Eseyin , Olorunfemi (Nigerian Journal of Pharmaceutical and Applied Science Research, 2022)
Background: Antimalarial drug resistance is increasing in Sub-Saharan Africa. Natural phenolic compounds are known to have antimalarial activity and should be harnessed to reduce the malaria burden. A potential mechanism of schizonticidal action is the inhibition of Plasmodium falciparum lactate dehydrogenase. This study aimed to evaluate the binding affinity of natural phenolics and their derivatives on Plasmodium falciparum lactate dehydrogenase. Methods: 35 compounds were downloaded from the Protein Data Bank and their binding energy on Plasmodium falciparum lactate dehydrogenase was evaluated using Autodock tools. Derivatives of compounds with the best binding energy and pharmacokinetic parameters were designed using ChemSketch and their binding energy was obtained. The protein-ligand interaction was analyzed using Discovery Studio. Results: Curcumin had binding energy of -6.95kcal/mol, vitexin had binding energy of -7.44kcal/mol and daidzein had binding energy of -7kcal/mol. Two derivatives of curcumin had binding energy of -7.61kcal/mol, and -7.24kcal/mol. Two derivatives of vitexin had binding energy of -8.02kcal/mol and -7.48kcal/mol. These compounds had favorable biological and pharmacokinetic properties and possessed binding energy better than reference compounds; dihydroartemisinin(-6.8kcal/mol), quinine(-7.2kcal/mol), and chloroquine(-5.76kcal/mol). Conclusion: Derivatized compounds had antiplasmodial potential and in vitro, in vivo work should be done to ascertain their schizonticidal activity.